A Comparative Analysis of Male and Female Complex I Skill Performance in Beach Volleyball - Tsakiri, Marina; Marathokampitou, Nafsika; Gasteratos, Vasilios; Mazonakis, Alexandros; Drikos, Sotirios; Barzouka, Karolina; Sotiropoulos, Konstantinos (Physical Education Theory and Methodology, 2025)
Objectives. The objective of this study was to analyse and evaluate the performance of skill types among male and female players in Complex I. Materials and Methods. The study comprised 28 men’s and 26 women’s matches, representing the 32 national teams that participated in the FIVB World Tour Finals 2019. A total of 3624 Complex I sequences were recorded and assessed. Passing skills (reception and setting) were evaluated using a four-level tactical rating quality scale, while attacking hits were assessed using a five-level scale. The observer’s reliability test demonstrated a high correlation coefficient. Results. Male beach volleyball players generally exhibited higher quality (Quality Level–QL3) in serve reception and setting, as well as greater effectiveness (QL4) in attacking hits compared to women. Males used more frequently the basic forearm pass technique in reception (p=0.001), the overhead set (p=0.001) in setting, and the hard-driven ball (p=0.001) in attacking compared to females. In contrast, females used more frequently the side forearm pass and other techniques in reception (p=0.001 and p=0.001, respectively), the forearm setting (p=0.001), and the driven ball and poke shot techniques in attacking (p=0.001 and p=0.001, respectively). Furthermore, the higher the quality of serve reception, the better the quality of the setting (p<0.001), and the higher the quality of the setting, the more effective the attack (p<0.001) for both genders. Finally, the results showed that male athletes executed excellent settings more frequently than femaleathletes (p=0.02, p=0.001, and p=0.001, respectively), regardless of the quality level of the received serve. Conclusions. Male players were more effective than female players, as they primarily used the frontal reception technique, overhead setting, and powerful attacking hits, which enhanced the overall quality of their game. To generalize these findings, further research is recommended at different competitive and age levels.